PENGARUH MEDIA PEMBELAJARAN POWTOON TERHADAP MOTIVASI BELAJAR SISWA KELAS III DI SD NEGERI WILAYAH II KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Permata Sari Aco, Intan; Abdul Saman; Amir Pada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research uses a quantitative approach with a type of experimental research aimed at testing hypotheses or theories through measurement and analysis of numerical data. The main goal of experimental research is to determine cause-and-effect relationships between the variables studied. Research in the form of Quasi Experimental Design uses methods that do not fully control the variables that influence the research results, but can still provide useful information about the cause-and-effect relationships between the variables studied. Based on the problem formulation: (1) What is the description of the use of Powtoon learning media among class III students at SD Negeri Region II, Polewali District, Polewali Mandar Regency? (2) What is the description of students' learning motivation before and after using Powtoon learning media in class III of Region II Public Elementary School, Polewali District, Polewali Mandar Regency? (3) Is there an effect of using Powtoon learning media on the learning motivation of class III students at SD Negeri Region II, Polewali District, Polewali Mandar Regency? So this research aims to find out: (1) An overview of the use of Powtoon learning media in class III students at SD Negeri Region II, Polewali District, Polewali Mandar Regency (2) A description of students' learning motivation before and after using Powtoon learning media in class III at SD Negeri Region II Polewali District, Polewali Mandar Regency (3) The influence of using Powtoon learning media on the learning motivation of class III students at SD Negeri Region II, Polewali District, Polewali Mandar Regency.